PP51 Strengths And Limitations Of Migraine Management Guidelines In The USA and Europe: A Targeted Literature Review. (23rd December 2022) - Perry, Richard; Mills, Kayla; Ford, Janet H.; McCosh, Zach
Abstract : Introduction: Migraine, the second leading cause of disability worldwide, remains underdiagnosed and undertreated. Considering the high burden of migraine, we analyzed the strengths and limitations of existing migraine management guidelines. Methods: A targeted literature review was conducted using MEDLINE on 24 March 2021 to identify current migraine management guidelines (including policies and position statements) published in the English language from France, Germany, Italy, Spain, the United Kingdom, and the USA. This was supplemented by a gray literature search. Disease state or pharmacological management guidelines for adults with migraine comprising any of the following perspectives were included: health economics; payer; health technology assessment; treatment access; and impact of guideline implementation on economic or disease burden. Guidelines were analyzed using the Centers for Disease Control and Prevention (CDC) policy analytical framework, which comprises three domains: problem identification, policy analysis, and strategy or policy development, with ranking criteria for each. Results: Of 39 selected guidelines, 25 adequately identified problems related to migraine, 35 sufficiently reviewed the literature on migraine treatment, three failed to cite literature, and one lacked sufficient content. Twenty-three guidelines targeted healthcare professionals. Almost all guidelines lacked a stepwise migraine treatment approach; only the American Academy of Family Physicians guideline offered first- and second-line treatment options. Four guidelines mentioned current political forces, and coverage of economic or budgetary impact aspects was limited. Numerous guidelines described the substantial economic burden of migraine and were categorized as 'high' for benefits. Public health impact was categorized as 'high' for 28 guidelines and budgetary impact was rated as 'more favorable' for 27 guidelines. Thirteen guidelines defined a strategy for the intended purpose. Only the United States Department of Health and Human Services pain management guideline met all of the CDC criteria. Conclusions: Future policies on migraine management may benefit from the inclusion of information on economic data, political feasibility, and public health impact. Furthermore, migraine management guidelines could potentially be improved by considering a comprehensive treatment approach and guideline implementation, as well as addressing knowledge gaps in disease state, public health, and economic aspects.